PERBANDINGAN KINERJA RANDOM FOREST DAN SMOTE RANDOM FOREST DALAM MENDETEKSI DAN MENGUKUR TINGKAT STRES PADA MAHASISWA TINGKAT AKHIR - Vionita Oktaviani (2024)
In people's daily lives, stress is a real problem so it becomes an inseparable part. Individual unpreparedness in facing academic demands can result in stress as a psychological disorder. In this case, academic stress is stress experienced by students, especially final year students. The presence of a lot of pressure from economic, academic and social conditions can trigger stress for final year students. This research aims to classify the stress level diagnosis of final year students by comparing the best performance between Random Forest and SMOTE Random Forest. The data processed in this research is data produced by a questionnaire containing 14 questions aimed at final year students who are carrying out their thesis. As for the results of this research, it was concluded that the Random Forest method using SMOTE was able to influence and improve the evaluation of case study classification for final year student diagnosis with an accuracy of 71%, precision of 72% and recall of 71% on a 80% distribution of training data, 20 % test data and K value = 5.